The Influence Of Accounting Information Systems In Improving The Effectiveness Of SMEs Financial Planning - Husnul Khuluq; Lilik purwanti; Zaki Baridwan (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study has two focus, first able to know the determinants that affect the satisfaction of users and their effect on the effectiveness of the financial planning process. To find out this is used a modification of the success of technology -based accounting information systems. The second focus of this research is able to show the success of the implementation of accounting information systems in Malang City SMEs by referring to IS Success Models. Methodology/approach: The population in this study is MSMEs in Malang City, which have been registered with the Cooperatives, Industry and Trade Service (DISKOPINDAG) and have used the smart cashier financial recording system. using a non-probability sampling method. This study uses SEM-PLS to analyze data, with validity tests, reliability tests, outer model tests, inner model tests and hypothesis tests. Findings: Research found that the quality variable of information, perception of use, trust has a positive effect on user satisfaction, while system quality variables do not have a positive effect on user satisfaction and user satisfaction have a positive effect on the effectiveness of the financial planning process. Practical implications:  Regarding the impact of the use of accounting information systems on the effectiveness of the financial planning process in Malang City SMEs, it can be used as an evaluation material for Malang City DiscountPindag in assessing the success of the AIS implementation of the user satisfaction of the system. Originality/value: Researchers make modifications to the success model of technology -based accounting information systems. The addition of variable perception of use and trust becomes renewal in this study. Then it can be seen whether the user of the level of trust application and the use of the application used for the financial planning process on MSMEs.